The Impact of the COVID-19 Lockdown on Coaches’ Perception of Stress and Emotion Regulation Strategies - Santi, Giampaolo; Quartiroli, Alessandro; Costa, Sergio; di Fronso, Selenia; Montesano, Cristina; Di Gruttola, Francesco; Ciofi, Edoardo Giorgio; Morgilli, Luana; Bertollo, Maurizio (Frontiers in Psychology, 2021)
The recent global outspread of the COVID-19 pandemic has influenced the lives of people across countries including athletes, coaches and supporting staff. As everybody else, coaches found themselves constrained to an at-home self-isolation, which limited their ability to normally engage with their profession and to interact with their athletes. This situation may also have affected their own psychological well-being. With this study, we explored coaches’ perceptions of stress in relation to their emotion regulation strategies depending upon their gender and competitive level (elite vs non-elite). More importantly, we explored the impact that the lockdown situation had on such strategies as well as their perception of stress. A sample of 2272 Italian coaches were surveyed during the period of lockdown. Two MANOVAs were completed to observe the potential differences in the coaches’ emotion regulation strategies and perception of stress. Finally, a mediation analysis, through Structural Equation Modeling (SEM) techniques, was run to assess how coaches’ emotion regulation strategies mediated the impact of COVID-19 emergency upon their perception of stress. Significant gender-based differences emerged in terms of emotional regulations, with men adopting more suppression. No differences by competitive level were found. In terms of perceived stress, men and elite coaches showed to be more in control of the situation (positive stress), while women experienced more negative stress than men. The mediation analysis evidenced how the experience of dealing with the COVID-19 emergency appeared to significantly increase the coaches’ perception of stress with their emotion regulation strategies playing a mediating role. In particular, reappraisal resulted more effective in helping coaches to reduce their perception of stress.